(untitled) (The Journal of Ad-din Women’s Medical College, 2025)
Introduction: Various factors contribute to knowledge, attitudes, and practices toward family planning practices in rural Bangladesh. Unfortunately, studies on the knowledge, attitude, and practices of Bangladeshi nationals in a rural setting are not sufficient. Objective: This study aimed to #nd out people’s knowledge, attitudes, and practices for getting family planning services in rural areas of Bangladesh. Materials and methods: A qualitative descriptive study was employed to follow a semi-structured questionnaire format. A total of 36 participants were interviewed from an upazila. Relevant works of literature were reviewed to enhance our understanding of the issue in question. The questionnaires were pretested before finalization. Results: All of the 36 participants were concerned regarding family planning but 16 (44.44%) of them were currently practicing, and 8 (2.22%) of them never used any of them in their conjugal life. Of all users, the Pill was the most favorite method 24 (82.76%). Condom 2 (6.9%), Injectable 1 (3.45%), Vasectomy 1 (3.45%), and Withdrawal 1 (3.45%) methods were common in the community. Though interested in using the methods, 32 (88.89%) participants didn’t know the benefits and side effects of using them. The majority of 30 (83.33%) of them got information regarding family planning from family members, and the rest of them were from media 6 (16.67%), health workers 5 (13.89%), and neighbors 8 (22.22%). Of those who used, 23 (85.18%) of them collected family planning materials from local pharmacies and the rest of them got them from hospitals 6 (22.22%) or, other #eld workers 3 (11.11%). Though their conjugal life varied but majority of them 23 (63.88%) had 1 or, 2 children. The majority of the participants 12 (33.33%) were between 14-28 years of age group, 34 (94.44%) of them were housewives and most of them had completed secondary level 25 (69.44%). Conclusion: We can have regular meetings in the community with users and service providers to make our knowledge and practices better. People of all ages, genders, and different incomes need to be involved to support services that are based on solid evidence. We need to teach and talk a lot about ways to plan your family and the services available for it. The Journal of Ad-din Women’s Medical College; Vol. 12 (2), July 2024; p 15-20